En skæbneanekdote fra Berliner Illustrierte: Omkring Vinter-Eventyrs udgivelse og udslettelse i Hitler-Tyskland - Behrendt, Poul (Danske Studier, 2024)
Based on the discovery that Isak Dinesen’s winter’s tale ‘The Pearls’ was already completed in December 1939, intended as a part of a forthcoming collection of stories carrying the title Anecdotes of Destiny, the tale is reinterpreted as a skæbneanekdote in which the steps of the »strange warfare« between the parties of a matrimonial mésalliance in Copenhagen 1863 converges with the chain of events leading up to the disastrous war between Denmark and Germany in 1864. The point of departure is the discovery of a German translation of the original version of ‘The Pearls’, made in 1940, which in October 1943 was published as ‘Eine Geschichte vom Schicksal’ in one of the most influential and propagandistic newspapers in the Third Reich, the weekly Berliner Illustrierte Zeitung. Previously, every convergence with the socalled Krieg um Schleswig-Holstein had been eliminated from the story by German censorship. Thus, the following article has two main aims: Firstly, to prove the potentially self-destructive consequences of the author’s wish for having Winter’s Tales published during the midst of a world war as an unpolitical bird migration across the heads of the antagonistic powers of that same world. Secondly, to identify the kernel of a uniquely modern literary endeavour, manifesting itself through the genesis of Isak Dinesen’s third book with its double designation of the stories as partly (winter’s) tales, partly anecdotes (of destiny) – or rather: partly anti-fairy tales; partly frictions between fictional characters and particular historical events.